(untitled) (Research, Society and Development, 2023)
When approaching the dynamism of a given social problem, there are several analysis techniques. The purpose of this article is to address the Content Analysis technique applied to the constructs presented. As a general objective, it sought to verify whether ISP, CSR and ESG are related and whether their inflections are proactive or defensive in the context of social innovation. Specifically, we sought to understand this inflection based on Content Analysis developed by Bardin. The Brundtland report indicated that poverty in Third World countries and high consumerism in First World countries represented the fundamental causes that prevented equal development in the world and, consequently, produced serious environmental and social crises. This thought caused changes in behavior in corporate society, where priorities began to be set in the context of Corporate Social Responsibility (CSR), Private Social Investment (ISP) and, finally, the much talked about Environmental Social and Governance (ESG). It is concluded that the social dimension understood in this study assumes the concern with the unsatisfied demands of society, thus causing civil society to focus on improvements in certain locations based on their involvement in the processes of economic development and social, through cooperation between the actors involved and the formalization of social networks or partnerships. It is expected to contribute to clarifying the peculiarities of the issues raised and analyzed by this technique, thus demonstrating its peculiarities and responsibilities with regard to the so-called social innovation.